KAJIAN ANALISIS WACANA: DALAM DUNIA KOMUNIKASI KEKUASAAN POLITIK DENGAN MASYARAKAT AWAM - Priyandono W. Atmojo, Maya Sekarwangi & (Transformasi, 2016)
Conversation Analysis is a field of study that examines the Discourse Analysis of socialinteraction in the community, the considers the discourse or conversation is a product of theinteraction.According to the analysis of Conversational perspective, the social reality nopresent objectively outside influence other social elements. A discourses was constructed byconversations that are face to face among participant when they involved in the process ofinteraction.This approach, including analyzing the verbal and nonverbal behavior in naturalisticsituation . Conversation analysis approach emphasizes how the message were organized,, usedand understood. In the communication process, we use the discourse to achieve what we hopeand for that we run it according to a certain rule, there are three fundamental issues associatedwith the analysis of this conversation.Key Word: communication, conversation, politik, analysis